Visualisasi Gedung STMIK Bandung Untuk Pengenalan Mahasiswa Baru Berbasis Augmented Reality (AR) Control dan Virtual Reality (VR) - Mina Ismu Rahayu; Faiqunnisa Faiqunnisa; Robby Herdiansyah (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2021)
The STMIK Bandung campus has various rooms, both classrooms, lecturer rooms, computer laboratory rooms, campus environment and other rooms. The process of searching for a room currently still relies on the information or information printed on the campus walls or asking the officers, campus employees and other students. An application has been built to visualize the STMIK BANDUNG building in the form of three-dimensional (3D) objects as a medium for delivering information on the campus environment from a building plan using AR (Augmented Reality) FPS (Control) and VR (Augmented Reality) technology. This application can make it easier for prospective students to obtain information about campus buildings or buildings owned by STMIK Bandung.  The software development methodology uses the waterfall method for problems that arise in the process of making FPS (Control) and VR (Augmented Reality) AR (Augmented Reality) applications. To design the system using UML (Unified Modeling Language). The application process is built using markerless, joystick, and virtual button techniques. The tools used are Unity3D as an editor and Blender is used for designing three-dimensional (3D) models.